一带一路背景下的国际中文教育研究动态与发展趋势: 2015-2025 - Shuang Zhang; Yue Jiang (Journal of Maobi, 2026)
By collecting 124 relevant literature on international Chinese language education research under the Belt and Road Initiative from the China National Knowledge Infrastructure (CNKI) database over the past decade (2015–2025), this study employs a scoping review methodology and utilizes CiteSpace visualization software to analyze its current status and development trends. The findings reveal that: 1) The overall development of international Chinese language education under the Belt and Road Initiative exhibits considerable fluctuation, broadly divided into two phases—rapid development and fluctuating adjustment—with 2018 serving as a turning point. 2) Research hotspots primarily encompass four areas: innovation in the “Chinese + Specialized Subject” composite talent cultivation model, regional and country-specific Chinese language education research, the transformation and high-quality development of Confucius Institutes, and the dissemination and advancement of Chinese language education. 3) In the context of the “Belt and Road Initiative”, international Chinese language education is characterized by diverse, broad, and dynamic research trends. Analyzing the current state and developmental trends of international Chinese language education research under the “Belt and Road” framework can provide valuable insights for future studies.